Modeling and forecasting Pakistan's inflation by using time series ARIMA models - Muhammad Abdus Salam; Shazia Salam; Mete Feridun (Colegio de Economistas de A Coru\~na, 2007)
This study attempts to outline the practical steps which need to be undertaken to use autoregressive integrated moving average (ARIMA) time series models for forecasting Pakistan's inflation. A framework for ARIMA forecasting is drawn up. On the basis of in-sample and out-of-sample forecast it can be concluded that the model has sufficient predictive powers and the findings are well in line with those of other studies. Further, in this study, the main focus is to forecast the monthly inflation on short-term basis, for this purpose, different ARIMA models are used and the candid model is proposed. On the basis of various diagnostic and selection & evaluation criteria the best and accurate model is selected for the short term forecasting of inflation.
Keywords: 330; Inflation; Prognose; ARMA-Modell; Pakistan